Pemanfaatan Batu Sungai Sa’dan Toraja Utara Sebagai Campuran Stone Matrix Asphalt Halus - Riki Adi Jansen; Nur Ali; Rais Rachman (Program Studi Teknik Sipil UKI Paulus-Makassar, 2020)
The Sa'dan River in Pangli, Sesean District, is one of the rivers in North Toraja Regency which has a source of stone which can be used as road pavement material. However, the material has never been tested labotarium as one of the requirements to be used as a material for pavement especially the mixture of Stone Matrix Asphalt (SMA). The purpose of this study was to determine the use of the Sa'dan river stone as a mixture of Fine Asphalt Stone Matrix using variations of asphalt content of 6.00%, 6.25%, 6.50%, 6.75% and 7.00%. The specifications used are the Specifications of Bina Marga 2018 Division 6 Revis1 1. Based on the results of testing stones from the Sa'dan river, Pangli sub-district, Sesean District, North Toraja Regency, it can be used as a material for a fine mixture of Stone Matrix Asphalt (SMA). The asphalt content that can be used in this mixing, can use asphalt levels between 6% to 7% but to get a more water-resistant mixture can use an asphalt content of 7%. The results of the Marshall immersion test using 7% asphalt content was 96.30%, this indicates that the mixture will withstand immersion for 24 hours.